2013
DOI: 10.1016/j.cgh.2012.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Many Patients Who Undergo Surgery for Colorectal Cancer Receive Surveillance Colonoscopies Earlier Than Recommended by Guidelines

Abstract: Background & Aims Patients treated with surgery for colorectal cancer (CRC) should undergo colonoscopy examinations 1, 4, and 9 years later, to check for cancer recurrence. We investigated the utilization patterns of surveillance colonoscopies among Medicare patients. Methods We used the Surveillance, Epidemiology and End Results (SEER)–Medicare linked database to identify patients who underwent curative surgery for colorectal cancer from 1992 to 2005 and analyzed the timing of the first 3 colonoscopies afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Several studies examined early receipt of colonoscopy after colonoscopy with normal results and found that 17–62% of CRC survivors received a second colonoscopy within 18 months of initial colonoscopy [27, 38, 40, 42] and 27% of survivors received a third colonoscopy within 2 years of a second normal colonoscopy [42]. These results were comparable to those obtained in a French sample where 29% of CRC survivors received colonoscopy at a period inconsistent with recommended guidelines [17].…”
Section: Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…Several studies examined early receipt of colonoscopy after colonoscopy with normal results and found that 17–62% of CRC survivors received a second colonoscopy within 18 months of initial colonoscopy [27, 38, 40, 42] and 27% of survivors received a third colonoscopy within 2 years of a second normal colonoscopy [42]. These results were comparable to those obtained in a French sample where 29% of CRC survivors received colonoscopy at a period inconsistent with recommended guidelines [17].…”
Section: Resultsmentioning
confidence: 73%
“…Twelve [2, 16, 2427, 29, 34, 3940, 42, 44] of the 34 studies did not provide data regarding the number of potentially eligible participants. Twenty-three studies [1523, 3033, 3539, 41, 43, 4547] explicitly reported how sample size was determined; for 11 [2, 2429, 34, 40, 42, 44] data were inferred (e.g., authors reported that sample was determined from a given administrative database) but not explicitly reported.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations